2009
DOI: 10.1080/15563650801938670
|View full text |Cite
|
Sign up to set email alerts
|

Ingestions of benzydamine-containing vaginal preparations

Abstract: This is the largest report of benzydamine ingestions. The outstanding feature was the high percentage of neurological manifestations in children and adults, mainly hallucinations, following the ingestion of an over-the-counter product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 15 publications
0
17
0
1
Order By: Relevance
“…BH preparates are over-the-counter in many countries and misuse reports are increasing [ 5 , 6 ]. In Turkey, BH preparates could be sold without prescription but Ministry of Health of Turkey prohibited selling BH preparates without prescription in 2012 after increased number of abusing cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BH preparates are over-the-counter in many countries and misuse reports are increasing [ 5 , 6 ]. In Turkey, BH preparates could be sold without prescription but Ministry of Health of Turkey prohibited selling BH preparates without prescription in 2012 after increased number of abusing cases.…”
Section: Discussionmentioning
confidence: 99%
“…Hallucinations were reported as a frequent symptom after ingestion of benzydamine-containing vaginal preparations [ 5 ]. Doğan et al reported a case report of visual hallucinations after BH overdose (total dose of 250 mg, 14.7 mg/kg) for suicide in a 11-year-old girl [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Он был синтезирован в Италии в 1964 г. и запущен в продажу в 1966 г. Бензидамин обладает болеутоляющим, противовоспалительным, местным анестезирующим и жаропонижающим свойствами [4]. Препараты бензидамина продаются во всем мире для симптоматического лечения ЛОР и гинекологических заболеваний [10]. Имеются сведения об антимикробном действии бензидамина, но они отрывочны и немногочисленны [11,12].…”
Section: бензидаминunclassified
“…Relatively little is known about the effects of BZY on the central nervous system. Symptoms such as hallucinations, dizziness and anxiety have been reported as a consequence of unintended systemic ingestion (Gómez‐López et al ; Ballesteros et al ; Settimi et al ; Acar et al ). Most important, there is evidence of recreational use of BZY in various countries, including Brazil, Italy, Poland and Turkey (Anand et al ; Opaleye et al , ; Settimi et al ; Balaban et al ; Barwina et al ).…”
Section: Introductionmentioning
confidence: 99%